Penerapan Profil Pelajar Pancasila Dalam Kurikulum Merdeka Pada Mata Pelajaran Pendidikan Pancasila di Sekolah Dasar - Shakina Shakina; Nashrullah Nashrullah; Sisriawan Lapasere; Arif Firmansyah; Muslim A.R (Institut Agama Islam Daruttaqwa Gresik, 2025)
This study examines the implementation of the Pancasila Student Profile within the Independent Curriculum for fifth-grade Pancasila Education at SDN 16 Dampelas. Using a qualitative descriptive method, data was collected through classroom observations, interviews with teachers and the principal, and document analysis. Findings indicate successful integration of core character values including religious devotion, global diversity awareness, mutual cooperation, independence, critical thinking, and creativity. These values were cultivated through daily routines such as pre-lesson prayers, group collaborative work, cultural appreciation activities, and classroom discussions.However, the study identified implementation challenges, particularly teachers' limited conceptual understanding of the Pancasila Student Profile framework, attributable to insufficient training opportunities under the new curriculum. Only a small percentage of teaching staff had received comprehensive curriculum training. The study recommends expanded professional development programs and ongoing mentoring to enhance implementation quality and ensure consistent application across all grade levels. The implication of this study highlights the need for improving teachers' understanding and skills in implementing the Pancasila Student Profile, particularly within the context of the Independent Curriculum. Comprehensive and ongoing training programs are essential to support the development of students' character in line with Pancasila values. This will strengthen the integration of national values and enrich students' learning experiences, resulting in a generation with strong competencies and character to face global challenges.